2019
DOI: 10.1038/s41386-019-0381-0
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawal from escalated cocaine self-administration impairs reversal learning by disrupting the effects of negative feedback on reward exploitation: a behavioral and computational analysis

Abstract: Addiction is regarded as a disorder of inflexible choice with behavior dominated by immediate positive rewards over longer-term negative outcomes. However, the psychological mechanisms underlying the effects of self-administered drugs on behavioral flexibility are not well understood. To investigate whether drug exposure causes asymmetric effects on positive and negative outcomes we used a reversal learning procedure to assess how reward contingencies are utilized to guide behavior in rats previously exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…Substance-dependent individuals have difficulties making adaptive decisions in dynamic environments (Ersche, Roiser, Robbins, & Sahakian, 2008; Fillmore & Rush, 2006; Ghahremani et al, 2011) and similar deficits have been observed in animals following exposure to drugs of abuse (Groman, Rich, Smith, Lee, & Taylor, 2018; Jentsch, Olausson, De La Garza, & Taylor, 2002; Schoenbaum, Saddoris, Ramus, Shaham, & Setlow, 2004; Zhukovsky et al, 2019) suggesting that the decision-making deficits observed in addicted individuals are, in part, a consequence of chronic exposure to drugs of abuse (Jentsch & Taylor, 1999; Lucantonio, Stalnaker, Shaham, Niv, & Schoenbaum, 2012; Schoenbaum, Roesch, & Stalnaker, 2006; Schoenbaum & Shaham, 2008). Recent studies in humans and animals have suggested that these deficits may be linked to abnormalities in the processing of negative outcomes.…”
Section: Neurocomputational Mechanisms Of Addiction-relevant Behaviorsmentioning
confidence: 69%
See 1 more Smart Citation
“…Substance-dependent individuals have difficulties making adaptive decisions in dynamic environments (Ersche, Roiser, Robbins, & Sahakian, 2008; Fillmore & Rush, 2006; Ghahremani et al, 2011) and similar deficits have been observed in animals following exposure to drugs of abuse (Groman, Rich, Smith, Lee, & Taylor, 2018; Jentsch, Olausson, De La Garza, & Taylor, 2002; Schoenbaum, Saddoris, Ramus, Shaham, & Setlow, 2004; Zhukovsky et al, 2019) suggesting that the decision-making deficits observed in addicted individuals are, in part, a consequence of chronic exposure to drugs of abuse (Jentsch & Taylor, 1999; Lucantonio, Stalnaker, Shaham, Niv, & Schoenbaum, 2012; Schoenbaum, Roesch, & Stalnaker, 2006; Schoenbaum & Shaham, 2008). Recent studies in humans and animals have suggested that these deficits may be linked to abnormalities in the processing of negative outcomes.…”
Section: Neurocomputational Mechanisms Of Addiction-relevant Behaviorsmentioning
confidence: 69%
“…Recent studies in humans and animals have suggested that these deficits may be linked to abnormalities in the processing of negative outcomes. Substance dependent individuals and rats with a history of drug self-administration appear insensitive to negative outcomes (Ersche et al, 2016; Groman et al, 2018; Zhukovsky et al, 2019), which may be related to the disruptions in negative prediction error signaling that have been observed in substance-dependent individuals (Parvaz et al, 2015; Tanabe et al, 2013).…”
Section: Neurocomputational Mechanisms Of Addiction-relevant Behaviorsmentioning
confidence: 99%
“…Within the laboratory setting, prior drug experience impairs the ability of subjects to adapt behavior following changes in reward contingencies. Rat (Jentsch and Taylor, 2001;Egerton et al, 2005;Stalnaker et al, 2009;Sokolic et al, 2011;McCracken and Grace, 2013;Zhukovsky et al, 2019), monkey (Jentsch et al, 2002;Wright et al, 2013;Seip-Cammack and Shapiro, 2014), and human studies have found that prior drug experience impairs reversal learning, resulting in marked perseveration following the switch (Fillmore and Rush, 2006;Verdejo-García et al, 2007;Ersche et al, 2008; but see Patzelt et al, 2014). Rodents previously exposed to drugs also fail to demonstrate proper contingency degradation or outcome devaluation, suggesting that drugs of abuse disrupt flexible value-based decision-making (Dickinson et al, 2002;Miles et al, 2003;Schoenbaum and Setlow, 2005;Nelson and Killcross, 2006;Corbit et al, 2014; but see Hogarth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main finding of Zhukovsky et al [3] is that higher rates of escalation of cocaine-taking behaviors were associated in the reversal-learning task with an increase in the degree of exploration (e.g., β-inverse temperature parameter), and an increase in the probability of repeating an unrewarded choice following cocaine self-administration. In contrast, the probability that the rats would repeat a rewarded choice was not affected, indicating that higher rates of escalation in cocaine use was associated with a selective deficit in their ability to integrate negative outcomes into their choice.…”
mentioning
confidence: 97%
“…In their recent Neuropsychopharmacology article, Zhukovsky and colleagues [3] used a computational approach to interrogate the reinforcement-learning mechanisms that are altered following cocaine self-administration in rats. Zhukovsky et al first trained rats on a two-choice, spatial discrimination task whereby responses in one of the two locations was reinforced with delivery of food pellet.…”
mentioning
confidence: 99%